Congenital bifocal unilateral lentiginosis. - Greco, I.; Ciampo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
A case of sporadic congenital bifocal unilateral lentiginosis is reported and its differential diagnosis discussed.